2022
DOI: 10.5194/acp-22-14905-2022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: The Urmia playa as a source of airborne dust and ice-nucleating particles – Part 1: Correlation between soils and airborne samples

Abstract: Abstract. The emergence of desiccated lake bed sediments and their exposure to wind erosion as a consequence of climate change and drought in arid and semiarid regions of the world poses a growing hazard. Airborne dust originating from such soils can create health and environmental issues due to their high salt content and the presence of toxic elements. The aim of the present study is twofold, namely to investigate the newly emerged playa surfaces of western Lake Urmia (LU) in Iran and their contribution to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 114 publications
(137 reference statements)
2
9
0
Order By: Relevance
“…In Part 1 (Hamzehpour et al, 2022) of the manuscript, we showed that F het of the natural samples are negatively correlated to TC and pH. The increase in F het after carbonate removal confirms this negative correlation.…”
Section: Carbonate-removed (Cr) Samplessupporting
confidence: 54%
See 4 more Smart Citations
“…In Part 1 (Hamzehpour et al, 2022) of the manuscript, we showed that F het of the natural samples are negatively correlated to TC and pH. The increase in F het after carbonate removal confirms this negative correlation.…”
Section: Carbonate-removed (Cr) Samplessupporting
confidence: 54%
“…A detailed characterization of the samples has been given and discussed in Part 1 of this work (Hamzehpour et al, 2022). Here, we summarize the applied methods and replicate the findings with relevance to this study.…”
Section: Physicochemical Analysismentioning
confidence: 64%
See 3 more Smart Citations